2022
DOI: 10.1097/meg.0000000000002463
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic efficacy on noninvasive fibrosis progression in nonalcoholic fatty liver disease: a systematic review and network meta-analysis

Abstract: Background Fibrosis impacts long-term outcomes among patients with nonalcoholic fatty liver disease (NAFLD). Due to well-documented flaws associated with liver biopsy, there has been a recent emphasis on prioritizing noninvasive testing over liver biopsy for the assessment of fibrosis. Methods A comprehensive systematic review and frequentist random effects network meta-analysis was performed among randomized controlled trials reporting pharmacologic intervention in NAFLD. The primary endpoint was the absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Additionally, other FGF21 analogs besides PGBF may have different effects on improving NASH. A network metaanalysis evaluated the efficacy of PGBF compared to other drugs in treating NASH (38), and PGBF's treatment effect did not show particular advantages over other drugs in NASH treatment. However, this study only included indicators of liver fibrosis improvement, and there were differences in the liver function status of patients included in the studies, making it impossible to comprehensively evaluate the superiority or inferiority of PGBF in improving liver function compared to other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other FGF21 analogs besides PGBF may have different effects on improving NASH. A network metaanalysis evaluated the efficacy of PGBF compared to other drugs in treating NASH (38), and PGBF's treatment effect did not show particular advantages over other drugs in NASH treatment. However, this study only included indicators of liver fibrosis improvement, and there were differences in the liver function status of patients included in the studies, making it impossible to comprehensively evaluate the superiority or inferiority of PGBF in improving liver function compared to other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a meta-analysis conducted by Mantovani A et al confirmed the effectiveness of various GLP1 receptor agonist in reducing the percentage of hepatic fat [ 47 ]. Also Kovalic AJ et al in their meta-analysis proved that semaglutide is one of the most effective drugs to treat NAFLD, which was confirmed by elastography and non-invasive blood tests [ 48 ]. The same results were published in 2023 by Gu Y et al [ 49 ] Similar results to our study on FIB-4 decrease were obtained by Arai, T et al in their pilot study for oral semaglutide treatment [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the moment, though, it seems that semaglutide is not effective in resolving or ameliorating liver fibrosis once it is present [ 125 ], whereas it seems to decrease steatosis and liver inflammation in vivo in Ldrl −/− mice [ 126 ]. Comparative studies and meta-analyses are currently being carried out in order to identify the most effective drug and its posology, which seems to also vary according to the patients’ metabolic status and compliance [ 127 , 128 , 129 , 130 ].…”
Section: Possible Therapeutic Approachesmentioning
confidence: 99%